Identification and Cloning of waaF (rfaF) from Bordetella pertussis and Use To Generate Mutants of Bordetella spp. with Deep Rough Lipopolysaccharide - Allen, Andrew G. (American Society for Microbiology, 1998)
A DNA locus from Bordetella pertussis capable of reconstituting lipopolysaccharide (LPS) O-antigen biosynthesis in Salmonella typhimurium SL3789 (rfaF511) has been isolated, by using selection with the antibiotic novobiocin. DNA within the locus encodes a protein with amino acid sequence similarity to heptosyltransferase II, encoded by waaF (previously rfaF) in other gram-negative bacteria. Mutation of this gene in B. pertussis, Bordetella parapertussis, and Bordetella bronchiseptica by allelic exchange generated bacteria with deep rough LPS phenotypes consistent with the proposed function of the gene as an inner core heptosyltransferase. These are the first LPS mutants generated in B. parapertussis and B. bronchiseptica and the first deep rough mutants of any of the bordetellae.